Large Displacement Analysis of Shell Structures using the Absolute Nodal Coordinate Formulation - Hyldahl, Per Christian (Technical Report Mechanical Engineering, 2013)
This report will review and discuss thin rectangular ANCF shell elements. First, a thorough review of the kinematic descriptions used in the current thin rectangular ANCF shells is given. This review will also contain a derivation of the equations of motion. Subsequently, a novel ANCF shell finite element with dynamic mesh properties is reviewed. This element is characterized by being able to change element size during transient simulation. The following chapter contains a preliminary study of the kinematics and numerical performance of thin rectangular ANCF shell elements when used in a curved and distorted mesh. A more general comparison of current element formulations is also performed. The results from the ANCF elements are compared to solutions obtained using a traditional commercial finite element code. At the end, the content of this report is summed up in a conclusion, and the outline of future work is presented.